Essays Before a Sonata, The Majority, and Other Writings - Ives, Charles 1874-1954; Boatwright, Howard (New York Norton & Company, 1970)
The Essays Before a Sonata was conceived by Ives as a preface of sorts to the composition. Ives's musings also explore the nature of music, discuss the source of a composer's impulses and inspiration, and offer some biting comments on celebrated masters. The writings in this collection now featuring a comprehensive index-allow readers entry into the brilliant mind that produced some of America's most innovative musical works.
Keywords: Composing